JARGON POLITIK AGAMA DAN BUDAYA PASANGAN CALON KOSTER-ACE SEBAGAI MEDIA KOMUNIKASI POLITIK DALAM PEMILIHAN GUBERNUR BALI 2018 - Dewa Putu Agus Sanjaya Putr; I Nyoman Yoga Segara; I Gede Sutarya (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2021)
Since the year 1999, the election method applied in Indonesia was representative election. A great change occurred when Law number 32 year 2004 was legalized. As a result, politics in Indonesia also changed. The head of a region is directly elected by all people. During Balinese governor election in 2018, politic communicators start to focus the style of their politic communication by using cultural and religious political jargons to gain Balinese sympathy. Based on the illustration above, this research focuses on discussing about (1) the constructive material of political jargons which uses religion and culture as political communications during Balinese governor election 2018, (2) electors’ perception towards the use of religion and culture as political jargons during Balinese governor election 2018, (3) political communication models using religion and culture during Balinese governor election 2018. The theories applied in analyzing research problems are dramaturgy theory by Erving Goffman. This research employs qualitative method. By applying qualitative method, the data being analyzed is descriptive data in the form of written and verbal words and observable behavior performed by politicians. The study reveals the following results. First, the material of religious and cultural political jargons used by the candidates of Balinese governor are the use of Balinese alphabets, color symbols, and traditional clothes which are used as a tool in political dramaturgy during the campaign. Second, the electors’ perceptions on the use of political jargons as communicative media during Balinese governor elections is a positive thing. The result of the survey shows that the electors are interested in electing the candidate because of the religion and cultural jargons as political communicative media. Third, there are positive and negative outputs for the political communication model.